Maturation Defects in Temperature-sensitive Mutants of Sindbis Virus - Yin, Fay H. (1968)
Temperature-sensitive mutants of Sindbis virus, which synthesize viral ribonucleic acid (RNA) but not mature virus at the nonpermissible temperature, were selected for the study of viral maturation. Of these, three mutants which complement each other genetically were used. Two major proteins, the nucleocapsid and membrane proteins, located, respectively, in the viral nucleoid and membrane, were found in intact virions. In cells infected with wild-type Sindbis virus, four distinct types of viral RNA with sedimentation coefficients of 40S, 26S, 20S, and 15S were detected in constant distribution. The 20S RNA was ribonuclease-resistant, whereas the other types were ribonuclease-sensitive. The 40S RNA, identical to that obtained from the virion, was found associated with nucleocapsid protein as a subviral particle, which was assumed to be the nucleoid. Viral materials from cells infected with the mutants under nonpermissive conditions were compared with those from cells infected with wild-type virus, in terms of (i) the distribution of the different types of RNA, (ii) the association of infectious viral RNA into subviral particles, and (iii) the ability of infected cells to hemadsorb goose erythrocytes. According to these criteria, each of the three mutants demonstrated different maturation defects. Defective nucleocapsid proteins and membrane proteins may each account for one of the above mutants. The thrid mutant may have defects in a minor structural protein or possibly a maturation protein which is involved in the assembly of Sindbis virus.